Hawks, doves, and opportunistic opposition parties. (January 2014) - Williams, Laron K
Parliamentary regimes offer the unique opportunity for opposition parties to react to foreign policy by proposing no-confidence motions (NCMs). The threat of an NCM bringing down the government may be enough to induce pacific behavior by the executive. Yet, this simplistic characterization neglects the possible electoral motivations of opportunistic opposition parties. I develop a theory that opposition parties respond to involvement in international conflict by proposing NCMs as a tool to influence voters' opinions with an eye toward the next election. I develop two expectations based on policy disagreement and issue ownership that I use to explain the electorally motivated decision to propose NCMs following conflict. I test these expectations with a dataset of 14 European parliamentary democracies from 1970 to 2001. The empirical evidence suggests that the partisanship of both the government and opposition parties interact to create varying electoral incentives to propose NCMs based on issue ownership. Right-wing opposition parties are more likely to challenge than left-wing parties, and this effect is exacerbated when facing left-wing governments. This study has important implications that underpin a number of theories of the domestic causes of international conflict as well as implications for the study of party strategy.